Preparation of Simple Financial Statements at MSMEs Opak Sun Jaya Mandiri Factory - Surbakti, Delta Citra Lestari; Alifah, Rifatul; Irdianti, Ananda Jaya; Saraswati, Dwi (Indonesian Journal Publisher, 2025)
Financial statements are the most important thing and one of the foundations of support in the MSME business. Many MSMEs and companies have failed to run their businesses, due to constraints in the preparation of financial statements, this happens due to the lack of understanding of MSME actors in the importance of financial recording and simple financial statements. However, this is certainly wrong, because by recording this simple financial statement, it is certainly very useful and can be a basic step in making decisions to ledge business in the future. In this case, we conducted research on MSMEs of the Sun Jaya Mandiri opak factory located in Tuntungan I village, Pancur Batu District. This research aims to review and provide an understanding of financial statements. The method we used was to conduct interviews with the direct owners of the Opak Sun Jaya Mandiri Factory MSMEs and see firsthand the financial recording process of the factory. The results of the research we conducted show that the Sun Jaya Mandiri opak factory has implemented simple financial report recording quite well and clearly. In this case, of course, the owner of the Sun Jaya Mandiri opak factory already understands very well the importance of simple financial statements.